1D- and 2D-matrices scintillation elements on the crystals base ZnSe(Te), CdWO₄, CsI(Tl), Bi₃Ge₄O₁₂ - Ryzhikov, V.D.; Galkin, S.N.; Voronkin, E.F.; Zelenskaya, O.V.; Chernikov, V.V.; Pirogov, E.N.; Kozin, D.N.; Lisetskaya, E.K.; Danilenko, V.L. (Functional Materials, 2004)
Results are presented of light output and uniformity of scintillation parameters of 1D and 2D-matrices for different conditions of their preparation. It has been shown that with grinded scintillators based on ZnSe(Te) and CdWO4 light output is higher as compared with the polished ones. Energy resolution and light output has been measured for 2D-scintillators on the ZnSe(Te) base for a-particles from 235Pu. Advantages of 2D-scintillators over monolithic scintillators are shown.